2019
DOI: 10.1002/admt.201900752
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐On‐Patterning of Sn–Pb Perovskite Photodiodes on IGZO Transistor Arrays for Fast Active‐Matrix Near‐Infrared Imaging

Abstract: features for developing high-performance X-ray imagers and ultraviolet sensors. [3] For imaging application, IGZO TFTs were mainly integrated with amorphous silicon and organic photodiodes, [3c,e,4] the spectral of which were usually limited to visible light detection. Large-area, active-matrix infrared sensing, therefore, remains a challenge.Organic-inorganic hybrid perovskites possess excellent optoelectronic properties with high absorption coefficient, high charge carrier mobility, long carrier diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Although many lowcost fabrication methods, such as the inkjet printing method, [53] blade coating method, [48] rolltoroll printing method, [88] and spraycoating method, [49] have been exploited to prepare the largearea perovskite photo detector arrays, the crystallization quality of asfabricated perovskites is still poor and the crosstalk between pixels is also a problem, which need to be further improved. In addi tion, the templateguided selfassembly method [47,54,55,85,86] and the hydrophilic-hydrophobic surfaceinduced selfassembled patterning method [51,57,58,102] also need to be further developed for the industrial production of perovskite image sensors due to their great potential for the fabrication of highresolution perovskite image sensors. Thirdly, color image sensing is also very significant for the practical applications of perov skite image sensors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many lowcost fabrication methods, such as the inkjet printing method, [53] blade coating method, [48] rolltoroll printing method, [88] and spraycoating method, [49] have been exploited to prepare the largearea perovskite photo detector arrays, the crystallization quality of asfabricated perovskites is still poor and the crosstalk between pixels is also a problem, which need to be further improved. In addi tion, the templateguided selfassembly method [47,54,55,85,86] and the hydrophilic-hydrophobic surfaceinduced selfassembled patterning method [51,57,58,102] also need to be further developed for the industrial production of perovskite image sensors due to their great potential for the fabrication of highresolution perovskite image sensors. Thirdly, color image sensing is also very significant for the practical applications of perov skite image sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The image sensor with a 6 × 6 photodetector array also demonstrated the potential imaging application by detecting the red light (650 nm) image of the letter "H" (Figure 12f). Then, Wang et al [102] reported the synthesis of Sn-Pb perovskite film arrays on the TFT arrays by a spinonpatterned deposition with a perfluoro(1butenyl vinyl ether) polymer (CYTOP)assisted hydrophilic-hydrophobic surfaceinduced growth (Figure 12g). A NIR image sensor based on a Sn-Pb perovskite film array was fabricated (Figure 12f), which showed a broad photore sponse range of 300-1000 nm, a high specific detectivity of 10 11 Jones at 850 nm, as well as the rise and decay times of 19 and 13 ms, respectively.…”
Section: D Perovskite Polycrystalline Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] Therefore, since metal oxide semiconductors do not require an additional crystallization process, the fabrication process of oxide TFTs is less complicated than that of Si‐based TFTs. [ 34 ]…”
Section: Fundamental Principle Of Metal Oxide Phototransistorsmentioning
confidence: 99%
“…Recently, phototransistors with a hybrid structure in which such perovskite is stacked together with an oxide semiconductor have been reported. [ 114–119 ]…”
Section: Classification Of Metal Oxide Phototransistors By Absorption Layermentioning
confidence: 99%